2021
DOI: 10.1111/gbb.12769
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping identifies a locus linked to striatal dopamine and points to collagen IV alpha‐6 chain as a novel regulator of striatal axonal branching in mice

Abstract: Dopaminergic neurons (DA neurons) are controlled by multiple factors, many involved in neurological disease. Parkinson's disease motor symptoms are caused by the demise of nigral DA neurons, leading to loss of striatal dopamine (DA). Here, we measured DA concentration in the dorsal striatum of 32 members of Collaborative Cross (CC) family and their eight founder strains. Striatal DA varied greatly in founders, and differences were highly heritable in the inbred CC progeny. We identified a locus, containing 164… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…In agreement with our findings, it has been previously reported that the expression of collagen type IV increases during aging in the human brain, where it accumulates in the basal lamina of cerebral microvessels, therefore, it is considered as a major risk factor for the development of stroke and vascular dementia [9]. Notably, in mouse brain, expression levels of collagen type IV α6 chain followed the expression of Sox2, a key regulator of neurogenesis [37,38]. In the brain of N. furzeri, we also observed a parallel age-related increase in col4a1 and sox2, showing that the functional relationship of these two genes might be conserved in this model organism, in which they could possibly be implicated in neuronal physiology (e.g., axon guidance and neurite outgrowth), as already shown in zebrafish [12].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, it has been previously reported that the expression of collagen type IV increases during aging in the human brain, where it accumulates in the basal lamina of cerebral microvessels, therefore, it is considered as a major risk factor for the development of stroke and vascular dementia [9]. Notably, in mouse brain, expression levels of collagen type IV α6 chain followed the expression of Sox2, a key regulator of neurogenesis [37,38]. In the brain of N. furzeri, we also observed a parallel age-related increase in col4a1 and sox2, showing that the functional relationship of these two genes might be conserved in this model organism, in which they could possibly be implicated in neuronal physiology (e.g., axon guidance and neurite outgrowth), as already shown in zebrafish [12].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the observed resistance to the PD-like phenotype in C57- En1 +/− mice is not due to a neuronal reserve in the SNpc exerting a buffering effect, but rather due to other mechanisms. Indeed, instead of SNpc cell numbers, cellular function and morphology may be more important for motor function, and the Collaborative Crossing Consortia have reported that low performance on motor tests is associated with striatal axonal branching rather than TH + area in the SNpc ( Thomas et al, 2021 ). Moreover, we detected no differences between C57 and OF1 in gene expression characteristic for mature dopaminergic neurons, suggesting that the difference in neuron number does not have an impact on relative transcript counts from dopaminergic neurons in this model.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the observed resistance to the PD-like phenotype in C57- En1 +/- mice is not due to a neuronal reserve in the SNpc exerting a buffering effect, but rather due to other involved mechanisms. Instead of SNpc cell numbers, cellular function and morphology may be more important for motor function, and the Collaborative Crossing Consortia reported that low performance on motor test was associated with striatal axonal branching rather than TH + area in the SNpc (Thomas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%